Can the official soccer game be considered the most important contribution to player`s physical fitness level? - Sporis, G.; Jovanovic, M.; Omrcen, D.; Matkovic, B. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: During competitive soccer match play, elite players are subdued to vigorous physical and psychological strains. Thus, some changes in overall physical fitness can be expected. The objective of this paper was to determine whether official games influence physical fitness in soccer players. METHODS:The participants were divided according to the number of minutes spent in the game as well as according to some additional criteria into starters (STA; N.=33, >1000 minutes spent in the official game) and non-starters (NON; N.=31, <1000 minutes spent in the official game). Both groups participated in the initial (end of pre-season) and in the final testing procedures (one week after the end of the competition period). The total of 24 variables covered players` power performance, kicking the ball, aerobic capacity, agility and flexibility. RESULS: The STA group showed positive significant differences (P<0.05) from the NON group in 21 out of 24 variables. The most significant findings of this study point to the fact that official games help in maintaining and improving agility parameters (6 out of 7 tests) as well as in maintaining and improving overall power performance of soccer players which includes sprinting, jumping and kicking the ball. CONCLUSION: Due to specific physiological and psychological factors, official matches make it possible for the starters to develop the mentioned aspects to a higher level when compared to the non-starting team colleagues.